A Comprehensive Legal and Ethical Analysis of AI’s Integration into Digital Ecosystems under Cyber Law - Mr.Virender Singh; Dr. Monika Rastogi (Revista Electronica de Veterinaria, 2024)
The rapid integration of Artificial Intelligence (AI) into digital ecosystems presents a host of legal and ethical challenges that require urgent attention within the framework of cyber law. AI’s increasing presence across industries such as healthcare, finance, transportation, and governance has introduced a myriad of complex issues, particularly concerning liability, data protection, privacy, intellectual property, and ethical decision-making. From a legal perspective, one of the most pressing concerns is determining accountability for AI-driven decisions, especially when systems operate autonomously without human oversight. Issues of data privacy and protection are also critical, as AI systems rely on vast amounts of personal data, raising concerns about consent, data ownership, and the risk of data breaches. Furthermore, intellectual property rights related to AI-generated content remain uncertain, particularly regarding the ownership of creations produced by AI systems. Ethical considerations, including the potential for AI to perpetuate or exacerbate biases, discrimination, and unequal treatment, pose significant concerns about fairness, justice, and transparency. This paper delves into the intersection of AI and cyber law, analyzing the regulatory approaches taken in various jurisdictions, such as the European Union’s General Data Protection Regulation (GDPR) and emerging AI-specific legislation. By reviewing current legal standards, ethical frameworks, and the evolving nature of AI technology, this analysis seeks to propose a balanced and comprehensive legal approach that fosters innovation while safeguarding human rights, fairness, and transparency. Ultimately, it calls for the development of adaptive legal and ethical guidelines that can ensure responsible AI deployment within digital ecosystems while preventing misuse or harm.